Quality of Life of Families of Children with Developmental Disabilities - Stanisavljević, Saša (Specijalna edukacija i rehabilitacija, 2024)
Introduction. Quality of life can be defined as a concept that broadly measures one’s experience in relation to that person’s hopes and aspirations. This definition can be applied to both an individual and a family perspective. Objectives. This research aimed to examine the quality of life of families of children with developmental disabilities and the interrelationship between family quality of life and certain socio-demographic characteristics of the family and the child. The socio-demographic characteristics of the family and the child include family structure, i.e., the total number of family members, the number of adults and the number of children in the family; material conditions, i.e., average monthly income and number of family members who earn money; place of living; availability of family support services; as well as the type of developmental disabilities and the age of the child with developmental disabilities. Methods. The research sample consists of 42 parents of children with developmental disabilities, and the control group consists of 63 parents of children with typical development. The Family Quality of Life Scale was used to assess family quality of life (Beach Center Family Quality of Life Scale - Beach FQOL Scale; Beach Center on Disability, 2012). Results. The results of the research showed that families of children with developmental disabilities have a significantly lower level of family quality of life compared to families of children with typical development, with the Emotional Well-being domain being the worst rated. In an effort to understand differences in family quality of life, additional analyses were conducted on relationships with certain socio-demographic characteristics of families. Conclusion. The findings suggest that the quality of life of families of children with developmental disabilities is influenced by the average monthly income, family structure, and the use of family support services, while no relationship was found between the level of family quality of life and place of residence, the number of persons in the family providing for the family, the type of developmental disabilities and the age of the child with disabilities.